Estimation of the X/γ- ray shielding properties of different glass system using Monte Carlo Simulation - et. al., Ayano Shanko, MD, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to estimate the X-ray shielding properties of different glass systems using Monte Carlo Simulation. X-ray glass is also known as radiation shielding glass. Glass provides protection against the absorption of energy radiation. The shielding layer is formed by a high concentration of lead and barium. The mass attenuation coefficient, the effective atomic number and the effective electron density are used to determine the position of gamma-ray photons in matter. Shield characterization in terms of mass attenuation coefficient (μm), transmission fraction (T), effective atomic numbers (Zeff), half-value layer (HVL) and exposure build-up. factor (EBF) of a glass system is estimated by the Monte Carlo Simulation. The random sampling and statistical analysis are computed using the monte carlo simulation. Various external factors are considered as the input parameters. The different composition of the glass will be examined using the Monte Carlo simulation and the shielding capability would be determined for the various samples.